Performance evaluation based on strictness and leniency errors / Dr. Roziyana Jafri and Dr. Syahida Abd Aziz - Jafri, Roziyana; Abd Aziz, Syahida (Universiti Teknologi MARA, Kedah, 2022)
Performance management is vital to the human resource functioning of public as well as private organizations. Performance management involves a never-ending process of observing performance, setting goals, and attaining objectives (Aguinis et al., 2011). If an employee's performance management results are in question, it could have debilitating consequences for the individual as well as for the organization’s goals and strategic plan. This requires organizations, namely managers, to ensure that employees’ outputs and actions are congruent with the organization’s objectives. Consequently, when performance management is aligned with strategic goals, it contributes to the organization’s competitive advantage. Performance management necessitates examining the facts of work performance and being aware that human judgments usually have a margin of error (Erbasi et al.,2012). When an organization implements performance management throughout the year, numerous frequent errors occur. However, only two types of issues, namely strictness and leniency, affect the effective implementation of performance management and the emergence of biased presumptions. Employer and employee must collaborate to achieve the organization’s objectives and maintain a positive relationship. From the perspective of an organization, these errors have a negative impact on organizational performance since disgruntled employees maintain poor relationships with coworkers (Mansor et al.,2020). When employees are dissatisfied with performance management, these errors have an effect from the individual's standpoint. They believe they receive no benefit and will not remain with the organization for an extended period of time.